2012
DOI: 10.1177/0312896212449828
|View full text |Cite
|
Sign up to set email alerts
|

Gender perceptions of work-life balance: management implications for full-time employees in Australia

Abstract: This study reports on gender perceptions of work–life balance based upon a qualitative study carried out among 437 full-time working men ( N=245) and women ( N=192) in the Australian workforce in 2008. The participants were randomly selected from a wide range of occupations, and their perceptions of: (a) non-work issues; (b) work–life conflicts; (c) organisational support for WLB; (d) desired WLB options; and (e) management treatment were investigated. Findings indicate significant gender differences in all ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 60 publications
(93 reference statements)
2
15
0
Order By: Relevance
“…Findings from these qualitative work–family studies confirmed that in the majority of cases, gender differences were present in the accommodation of work–family needs (e.g. Burnett et al, ; Emslie & Hunt, ; Fujimoto, Azmat, & Haertel, ; Loscocco, ; Perrons, ). Examples of such differences include forgoing individual needs (Guendouzi, ), gendered time use (Rafnsdóttir & Heijstra, ), gendered family structure (Stalp & Conti, ), gendered household labour, parenting and caring roles (Crompton & Lyonette, ; Hilbrecht, Shaw, Johnson, & Andrey, ; Lowson & Arber, ; Windebank, ), gendered employment relations (Hantrais & Ackers, ; Turbine & Riach, ), and gendered family‐friendly policies/programmes (McDonald, Pini, & Bradley, ; Root & Wooten, ).…”
Section: Resultssupporting
confidence: 60%
“…Findings from these qualitative work–family studies confirmed that in the majority of cases, gender differences were present in the accommodation of work–family needs (e.g. Burnett et al, ; Emslie & Hunt, ; Fujimoto, Azmat, & Haertel, ; Loscocco, ; Perrons, ). Examples of such differences include forgoing individual needs (Guendouzi, ), gendered time use (Rafnsdóttir & Heijstra, ), gendered family structure (Stalp & Conti, ), gendered household labour, parenting and caring roles (Crompton & Lyonette, ; Hilbrecht, Shaw, Johnson, & Andrey, ; Lowson & Arber, ; Windebank, ), gendered employment relations (Hantrais & Ackers, ; Turbine & Riach, ), and gendered family‐friendly policies/programmes (McDonald, Pini, & Bradley, ; Root & Wooten, ).…”
Section: Resultssupporting
confidence: 60%
“…Australian research has observed that the traditional masculine 'ideal worker norm' predominates in many Australian workplaces, valuing workers who are willing and able to prioritise work over other life commitments such as care for children or elders (Albion 2004;Mcdonald, Bradley, and Brown 2009;Pocock, Charlesworth, and Chapman 2013). Such normative and gendered expectations are a central facet of organisational work-life culture (Fujimoto, Azmat, and Hartel 2013;Lewis, Gambles, and Rapoport 2007).…”
Section: The Current Studymentioning
confidence: 99%
“…Although gender differences were rather small, the result confirms previous findings showing that men and women differ as regards the goals they want to achieve by using WLB benefits. Previous research shows that when using benefits, men care more for free time, possibility to pursue their hobbies or to travel, whereas women appreciate the possibility to be available when their families need them [14][15][16]. It is worth noting again that our study included only SME employees.…”
Section: Discussionmentioning
confidence: 98%